2020
DOI: 10.1097/ta.0000000000002610
|View full text |Cite
|
Sign up to set email alerts
|

Mortality review of US Special Operations Command battle-injured fatalities

Abstract: BACKGROUND Comprehensive analyses of battle-injured fatalities, incorporating a multidisciplinary process with a standardized lexicon, is necessary to elucidate opportunities for improvement (OFIs) to increase survivability. METHODS A mortality review was conducted on United States Special Operations Command battle-injured fatalities who died from September 11, 2001, to September 10, 2018. Fatalities were analyzed by demographics, operational posture, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
68
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 12 publications
4
68
1
3
Order By: Relevance
“…62 Similarly, a recent comprehensive analysis of US Special Operations Command battle-injured fatalities found that time to surgery and prehospital blood transfusion were the primary opportunities for improvement to increase survivability. 63 These findings strongly support prehospital transfusion in this setting. Therefore, hemostatic agents for prehospital and early in-hospital administration are particularly important.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…62 Similarly, a recent comprehensive analysis of US Special Operations Command battle-injured fatalities found that time to surgery and prehospital blood transfusion were the primary opportunities for improvement to increase survivability. 63 These findings strongly support prehospital transfusion in this setting. Therefore, hemostatic agents for prehospital and early in-hospital administration are particularly important.…”
Section: Discussionmentioning
confidence: 53%
“…Among medically evacuated US combat causalities in Afghanistan, blood product transfusion prehospital was associated with greater 24‐h and 30‐day survival than delayed transfusion or no transfusion 62 . Similarly, a recent comprehensive analysis of US Special Operations Command battle‐injured fatalities found that time to surgery and prehospital blood transfusion were the primary opportunities for improvement to increase survivability 63 . These findings strongly support prehospital transfusion in this setting.…”
Section: Discussionmentioning
confidence: 80%
“…Hemorrhage remains to be the principal cause of preventable death on the battle eld [1,2]. A variety of technologies have been directed toward control of bleeding including tourniquets, direct pressure, hemostatic dressings, and circulatory volume replacement [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhage remains to be the principal cause of preventable death on the battlefield 1 , 2 . A variety of technologies have been directed toward control of bleeding including tourniquets, direct pressure, hemostatic dressings, and circulatory volume replacement 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%